Cognition in aged rhesus monkeys: effect of DHEA and correlation with steroidogenic gene expression. (24th November 2016) - Sorwell, K. G.; Renner, L.; Weiss, A. R.; Neuringer, M.; Kohama, S. G.; Urbanski, H. F.
Abstract : Estradiol supplementation has been shown to enhance cognitive performance in old ovariectomized rhesus macaques ( Macaca mulatta ). To determine if similar benefits could be achieved in perimenopausal animals using alternative hormonal supplements, we administered dehydroepiandrosterone (DHEA) to old ovary‐intact female rhesus macaques for ∼2.5 months. Using computerized touch screen memory tasks, including delayed response (DR) and delayed matching‐to‐sample (DMS), we observed improved performance with time in all of the animals but failed to detect a significant effect of DHEA. On the other hand, gene expression profiling disclosed a significant correlation between cognitive performance and the expression of several steroidogenic and steroid‐responsive genes. The DR performance was positively correlated with hippocampal expression of AKR1C3 and STAR and negatively correlated with the expression of SDRD5A1 . A positive correlation was also found between DMS performance and prefrontal cortical expression of AKR1C3 and a negative correlation with STAR, as well as a negative correlation with the hippocampal expression of HSD11B1 and NR3C1 . Taken together, the results suggest that steroidogenic gene regulation within the brain may help to maintain cognitive function during the perimenopausal transition period, despite a decline in sex‐steroid levels in the circulation. Abstract : Correlation of cognitive performance with gene expression in the hippocampus and prefrontal cortex of aged female rhesus macaques.